Client responses to therapist statements as behavioural requests. - Sterner, Irit. (University of Ottawa (Canada), 1990)
Psychotherapists' statements may be conceptualized and described in different ways, depending on which aspects of the statements are highlighted. Traditionally, therapist statements have been described in terms of techniques that serve, for example, interpretative, reflective, or supportive functions. From a psycholinguistic or an interactional communications perspective, therapist statements may also be understood as inviting or instructing the client (directly or indirectly) to respond in a particular manner and to carry out given behaviours. Accordingly, the primary purposes of the present research were (1) to examine therapist statements as potentially containing requests for verbal behaviour, and (2) to test hypotheses regarding clients' responses to these antecedent behavioural requests. The data consisted of 12 sessions; two sessions from the beginning, middle, and end of two therapy cases, one Gestalt and the other psychodynamic. Raters identified therapist statements that contained requests for verbal behaviour and specified the nature of these requests. The requests were then organized into a general set of categories for each therapist. A second team of raters ascertained the goodness of fit between the therapist statements and the categories to which they had been assigned. A third team of judges rated the clients' responses to the therapists' antecedent requests on a four-point scale of conformity. The results indicated that a large proportion of therapist statements contained requests for verbal behaviour (66.3%). While some requests were communicated explicitly as such, others were implicit in the therapists' statements. Some categories of requested verbal behaviour were common to both therapists while others appeared to be unique to a particular therapeutic approach. Both therapists invited certain categories of verbal behaviour more often than others. The findings also showed that the level of client conformity to the therapists' antecedent requests was high in general (82% of client responses in the Gestalt case, 98% in the psychodynamic case), and that this high level was relatively stable and consistent across sessions. In the Gestalt case, the degree of conformity was found to vary depending on the type of verbal behaviour requested by the therapist. Nevertheless, a high level of conformity was reflected in all the categories in one case, and most of the categories in the other case. Contrary to expectations, the findings did not show (1) a strong upsurge in client opposition corresponding to particular stages of therapy, or (2) stage differences in the extent of conformity or type of opposition. The findings of this investigation are discussed in terms of their implications for clinical practice and future research.
Keywords: Speech Communication.